Reframing culture in youth mental health: introducing a neurocultural framework through participatory arts and emotional scaffolding - Weinrabe, Angé; Malik, Atteqa; Cochrane, Tom; Khan, Mariam; Murphy, Dominic; Smith, Jessica (Frontiers in Education, 2025)
IntroductionYoung people are experiencing an escalating global mental health crisis, intensified by the effects of COVID-19, cultural disconnection, and the limited fit of conventional clinical models with diverse populations. While biomedical and psychological models remain essential, they often underplay the symbolic, sensory, and relational dimensions of emotional life. This review explores how young people interpret and regulate their mental health through expressive, symbolic, and sonic practices. It proposes that the Culture-as-Practice (CAP) framework can complement existing approaches by offering a more integrated understanding of how cultural participation supports wellbeing.MethodsA narrative review informed by the CAP framework, which extends the Culture-as-Interaction (CAI) model, was conducted to evaluate how participatory cultural practices function as affective technologies. Literature published between 2010 and 2025 was systematically identified from five databases and screened using PRISMA-informed protocols. Data were analyzed thematically with CAP and CAI constructs. Two case studies–Whānau Ora (New Zealand) and Giving Emotions Meaning through Arts and Health (GEMAH) (Pakistan and Australia)–were selected to illustrate how CAP explains mechanisms through which cultural participation supports emotional wellbeing.ResultsParticipatory arts such as music, storytelling, and ritual were found to serve as cultural technologies that foster emotional regulation, identity coherence, and social connection. Sonic and symbolic practices created co-regulatory fields of belonging, effects often absent in conventional clinical models. CAP aligned with these findings by offering a theoretical lens to explain why such practices work, reframing them as structured culture as affective technologies rather than incidental engagement.DiscussionCulture-as-Practice provides more than an alternative to biomedical models. It offers an explanatory framework for why participatory, culturally grounded practices support youth mental health and wellbeing. By positioning emotional regulation as relationally and symbolically scaffolded, CAP highlights opportunities for integrating creative and communal practices into trauma-informed, culturally resonant interventions across schools, communities, and clinical settings.